Development of Contextual Visual Media in Increasing the Scientific Literacy of Middle School/ MTs Students - Euis Sri Hastuti; Anna Fitri Hindriana; Agus Yadi Ismail (Quagga: Jurnal Pendidikan dan Biologi, 2025)
The low level of students ' scientific literacy abilities can be caused by learning habits that are still conventional . Developing digital- based learning media is a good learning media to use in learning in the era of the industrial revolution 4.0 and is believed to be capable to increase students ' scientific literacy . The aim of this research is to develop contextual visual media that can increase students ' scientific literacy . The method used in this research uses the ADDIE model developed by Dick and Carry . The results of the research is in the form of contextual visual media which was developed in five stages , namely analysis was carried out by observing and interviewing school principals and subject teachers , design was carried out by making stories boards , at the development stages validation was carried out by material experts and learning design experts , implementation was carried out in the experimental class , and the evaluation stages was carried out by improving the visual media developed according to input from the validator team . The validity test results are in the very good category , so the visual media developed is suitable for use in research . Based on the t test results of 0.001, these results indicate that the hypothesis is accepted , so it can be concluded that there is an increase in scientific literacy after learning activities using the developed contextual visual media.